RUMAH GADANG DALAM KARYA SENI RELIEF KAYU - Yovie Febrian Piko, Drs. Efrizal, M.Pd., Drs. Irwan, M.Sn. (Serupa The Journal of Art Education, 2017)
The purpose of creation of this final work is to preserve the culture back Minangkabau in West Sumatra into wood relief artwork. Rumah Gadang here is related to the Minangkabau culture that needs to be preserved. Where the existence of Rumah Gadang in West Sumatra faded due to the influence of foreign culture. The Rumah Gadang is currently only a symbol in West Sumatra, without re-running the traditions that are in it. Therefore Minangkabau young people no longer recognize the function or variety of forms of Rumah Gadang. This is interesting to be lifted in realizing Rumah Gadang with the theme of Rumah Gadang in relief wood artwork. Method for creating this thesis uses five phases: preparation, elaboration stage, synthesis stage, the stage of realization of the concept, and the stage of completion, as well as the latter held an exhibition of works of art wood reliefs. Technique used is technique of High Relief, Midle Relief and Low relief.Seven works are lifted back visualize the various forms of the Tower House is much reduced in West Sumatra because of the influence of foreign cultures. The seven works are: 1) Rumah Gadang Gajah Maharam, 2) Rumah Gadang Kajang Padati 3) Rumah Gadang Ampek Sibak Baju 4) Rumah Gadang Gonjong Anam Baanjuang 5) Rumah Gadang Surambi Papek Batingkek 6) Rumah Gadang Gonjong Ampek Batingkek 7) Rumah Gadang Surambi Aceh Bagonjong Duo.Kata kunci: Kayu, Rumah Gadang, relief.